Increase The Percentage of Coal Conservation Deposited in ROM Drainage Areas - Aifah Aifah; Ryan Afif Hendrawan; Fransiskus Bimantoro Agung; Jepri Victor (Jurnal Indonesia Sosial Teknologi, 2024)
The research aims to increase the conservation percentage of trapped coal in the ROM A1 drainage area from February to June 2024 by improving fine coal management and adding value to the conservation of PJP. This study also seeks to reduce penalties from fine coal blending into sellable products and minimize environmental pollution in the ROM A1 area. The study employs a descriptive method, focusing on implementing coal conservation in drainage areas by determining the scope of each conservation object. Root cause analysis using a Fishbone diagram was used to identify key improvement strategies for increasing coal conservation percentages. Initial observations in the ROM A1 drainage area revealed 6,829 tons of unpreserved fine coal, primarily due to rainwater runoff. The results showed that with proper implementation of conservation techniques, including the installation of fine coal traps and the centralization of fine coal in collection points, the conservation rate improved from 0% to 62% by April 2024. In tangible terms, 83 tons of fine coal, worth IDR 26,434,928, were saved, contributing to both environmental conservation efforts and economic benefits for the company. This study highlights the importance of continuous coal conservation efforts, especially in mining operations where environmental and financial impacts can be significant.